Resilience for food and nutrition security - Fan, Shenggen; Pandya-Lorch, Rajul; Yosef, Sivan (International Food Policy Research Institute, 2014)
Economic shocks including food price shocks, environmental shocks, social shocks, political shocks, health shocks, and many other types of shocks hit poor people and communities around the world, compromising their efforts to improve their well-being. As shocks evolve and become more frequent or intense, they further threaten people’s food and nutrition security and their livelihoods. How do we help people and communities to become more resilient, to not only bounce back from shocks but to also to get ahead of them and improve their well-being so that they are less vulnerable to the next shock? How do we get better at coping with—and even thriving—in the presence of shocks?